The last rose of Shanghai - Randel, Weina Dai (Lake Union Publishing, 2021)
1940. Aiyi Shao is a young heiress and the owner of a formerly popular and glamorous Shanghai nightclub. Ernest Reismann is a penniless Jewish refugee driven out of Germany, an outsider searching for shelter in a city wary of strangers. He loses nearly all hope until he crosses paths with Aiyi. When she hires Ernest to play piano at her club, her defiance of custom causes a sensation. His instant fame makes Aiyi's club once again the hottest spot in Shanghai. Soon they realize they share more than a passion for jazz, but their differences seem insurmountable, and Aiyi is engaged to another man. As the war escalates, Aiyi and Ernest find themselves torn apart, and their choices between love and survival grow more desperate. In the face of overwhelming odds, a chain of events is set in motion that will change both their lives forever.